Sleep Deprivation-Induced Blood-Brain Barrier Breakdown and Brain Dysfunction are Exacerbated by Size-Related Exposure to Ag and Cu Nanoparticles. Neuroprotective Effects of a 5-HT3 Receptor Antagonist Ondansetron - Sharma A.; Muresanu D.F.; Lafuente J.V.; Patnaik R.; Tian Z.R.; Buzoianu A.D.; Sharma H.S. (My University, 2025)
Military personnel are often subjected to sleep deprivation (SD) during combat operations. Since SD is a severe stress and alters neurochemical metabolism in the brain, a possibility exists that acute or long-term SD will influence blood-brain barrier (BBB) function and brain pathology. This hypothesis was examined in young adult rats (age 12 to 14 weeks) using an inverted flowerpot model. Rats were placed over an inverted flowerpot platform (6.5 cm diameter) in a water pool where the water levels are just 3 cm below the surface. In this model, animals can go to sleep for brief periods but cannot achieve deep sleep as they would fall into water and thus experience sleep interruption. These animals showed leakage of Evans blue in the cerebellum, hippocampus, caudate nucleus, parietal, temporal, occipital, cingulate cerebral cortices, and brain stem. The ventricular walls of the lateral and fourth ventricles were also stained blue, indicating disruption of the BBB and the blood-cerebrospinal fluid barrier (BCSFB). Breakdown of the BBB or the BCSFB fluid barrier was progressive in nature from 12 to 48 h but no apparent differences in BBB leakage were seen between 48 and 72 h of SD. Interestingly, rats treated with metal nanoparticles, e.g., Cu or Ag, showed profound exacerbation of BBB disruption by 1.5- to 4-fold, depending on the duration of SD. Measurement of plasma and brain serotonin showed a close correlation between BBB disruption and the amine level. Repeated treatment with the serotonin 5-HT3 receptor antagonist ondansetron (1 mg/kg, s.c.) 4 and 8 h after SD markedly reduced BBB disruption and brain pathology after 12 to 24 h SD but not following 48 or 72 h after SD. However, TiO2-nanowired ondansetron (1 mg/kg, s.c) in an identical manner induced neuroprotection in rats following 48 or 72 h SD. However, plasma and serotonin levels were not affected by ondansetron treatment. Taken together, our observations are the first to show that (i) SD could induce BBB disruption and brain pathology, (ii) nanoparticles exacerbate SD-induced brain damage, and (iii) serotonin 5-HT3 receptor antagonist ondansetron is neuroprotective in SD that is further potentiated byTiO2-nanowired delivery, not reported earlier. © 2015, Springer Science+Business Media New York.